Novel Encephalomyelitis-Associated Astrovirus in a Muskox (Ovibos moschatus) – a Surprise from the Archives - Boujon, Céline Louise; Koch, Michel Christoph; Kauer, Ronja Veronique; Keller-Gautschi, Elsbeth; Hierweger, Melanie Michaela; Hoby, Stefan; Seuberlich, Torsten (Acta Veterinaria Scandinavica, 2019)
Background: The small, single-stranded positive-sense RNA astroviruses are mostly known to be enteric viruses. In recent years, though, different astroviruses were reported in association with neurological disease in various species. In cattle, two distinct neurotropic astrovirus genotype species were described in numerous cases of nonsuppurative encephalomyelitis, with one of these viruses also reported in similar circumstances in several sheep. Here, we retrieved archived formalin-fixed, paraffin-embedded brain tissues of a muskox diagnosed with a comparable disease pattern in 1982 and investigated them for the presence of neurotropic astroviruses with various techniques. Results: Initially, tissue samples scored positive for both neurotropic astroviruses by immunohistochemistry; however, unexpected results with further immunohistochemical testing, in situ hybridization and qRT-PCR prompted us to submit an RNA extract from the animal’s brain material to next-generation sequencing. We were thus able to obtain the full genome of a novel astrovirus, muskox astrovirus CH18 (MOxAstV-CH18), whose closest relative is an enteric ovine astrovirus. Subsequently, viral RNA could be detected with a specific RT-PCR in the brain of the affected animal, but not in faecal samples from the current muskoxen herd of the animal park where the animal used to be kept. Conclusions: We identified a novel astrovirus in a historical case of a captive muskox with nonsuppurative encephalomyelitis. Unfortunately, our results and the fact that no material from organs other than of the nervous system was available do not allow any assumption about the epidemiology or pathogenesis of the virus. Still, these findings are yet another piece of evidence that the tropism and species specificity of astroviruses could be more deceptive than generally assumed.